Software quality engineering : a practitioner's approach - Suryn, Witold (Hoboken, N.J. : John Wiley : IEEE, 2014)
A concise, engineering-oriented resource that provides practical support to IT professionals and those responsible for the quality of the software or systems they develop. Software quality stems from two distinctive, but associated, topics in software engineering: software functional quality and software structural quality. This book studies the tenets of both of these notions, which focus on the efficiency and value of a design, respectively. It addresses engineering quality on both the application and system levels with attention to information systems (IS) and embedded systems (ES) as well as recent developments. Software Quality Engineering introduces the basic concepts of quality engineering like the nature of the engineering process, quality models and measurements, and evaluation quality, and provides a step-by-step overview of the application of software quality engineering in commonly recognized phases of the software development process. It also discusses management of software quality engineering processes, with special attention to budget, planning, conflict resolution, and traceability of quality requirements.
Preface ix 1 Why Software Quality Engineering? 1 -- 2 Software Quality Engineering: Making It Happen 35 -- 3 System and Software Quality Engineering: Some Application Contexts 139 -- 4 Trustworthiness of IT Systems and Services 151 -- Appendix Cost of Missing Quality: Case Studies 175 -- Index 191.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Computer software -- Quality control; Logiciels -- x; COMPUTERS -- Software Development & Engineering -- Quality Assurance & Testing; Computer software -- Quality control